The present participle and gender assignment in Swedish - Skrzypek, Dominika (Folia Scandinavica Posnaniensia, 2021)
The paper considers gender assignment of deverbal nouns, originally present participles, in Swedish. The perspective is diachronic. The corpus consists of a choice of Swedish texts from 1225-1732. The results show that nouns denoting entities ranking higher in the Animacy hierarchy show tendencies to be placed in the utrum gender (originally masculine and feminine genders) and nouns denoting mass, collective or abstract referents to be assigned neuter gender. This tendency is visible throughout the history of the Swedish language.